Urban Agriculture & Regional Food Systems Special Section: Improving Livability in Urban Areas: Examining Urban and Peri‐Urban Soil and Plant Management - Roberta Bulgari; Erdona Demiraj; Calogero Schillaci; Ahlem Tlili; Yushu Xia (Urban Agriculture & Regional Food Systems)
Abstract As urban agriculture increasingly becomes part of our regional food systems, its role in sustainable urban development grows. Urban agriculture can sustain food demand and contribute to food security, environmental sustainability, and community health. However, soil‐related factors in urban agricultural systems pose unique challenges not found in more rural environments, and issues such as soil fertility, soil biodiversity, soil contamination, and existing policy demand further investigation to deepen and enhance the potential contribution of urban agriculture to livability in urban areas. This special issue collects studies to support the need for sustainable soil management, crop diversification, and management strategies for optimal soil health and good crop yield and quality. In addition, the issue examines recent advances in remote sensing technologies and deep learning techniques that offer potential tools for soil health monitoring and plant disease detection related to existing plant‐based contamination, providing a way forward to make informed decisions for policy stakeholders and land planners. Combining these initiatives into urban planning and public health policies could have a considerable impact on urban well‐being and resilience.